INOVASI PENILAIAN PEMBELAJARAN BAHASA ARAB BERBASIS GAMES KAHOOT UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK DI MA DARUL ULUM REJOMULYO MAGETAN - Fauzia Nabila Zahida; Yunus Abu Bakar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Arabic language learning, particularly regarding listening skills (*maharah istima’*), is often perceived by students as difficult and tedious. At MA Darul Ulum Rejomulyo Magetan, the continued use of conventional paper-based assessment methods resulted in stagnant student learning outcomes, with many falling below the Minimum Mastery Criteria (KKM). Consequently, there is a need for digital technology-based assessment innovations—such as Kahoot games—to create an interactive, enjoyable, and motivating evaluation environment. This study aims to describe the implementation of Kahoot-based assessment innovation in Arabic language learning to enhance students' listening skills at MA Darul Ulum Rejomulyo Magetan. The study employs a Research and Development (R&D) approach within a naturalistic setting. Data collection was conducted through direct observation and interviews at the educational institution. By utilizing in-depth and meticulous interview and observation techniques, the researcher was able to obtain accurate data.The implementation of Kahoot as an assessment tool proved capable of rapidly increasing students' active engagement and motivation in Arabic listening activities. The use of multimedia features (music, images, and videos) in Kahoot encouraged students to examine questions closely and prevented boredom. Evaluation results from a class of 25 students showed that 20 achieved satisfactory scores (categorized as "very good"), only three scored below 60, and the remaining students demonstrated a significant upward trend compared to when printed media was used. Furthermore, the platform facilitates the analysis of answers and real-time monitoring of student scores for teachers. The innovation of using Kahoot games for Arabic language assessment proved effective and optimal, successfully dispelling the stigma that Arabic is a difficult subject. This online medium boosted student learning enthusiasm while simultaneously simplifying the evaluation process for teachers.